Factors of psychological well-being of Ukrainian women forced migrants - YURCHYNSKA, Hanna; MASELSKA, Liudmyla (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . With the beginning of a full-scale Russian-Ukrainian war, many of Ukrainian females were forced to leave Ukraine. Thus, the problem of maintaining their psychological well-being and returning to the country in the current situation and in the future is a case to be solved by both foreign and domestic scientists. The issues of determining the factors of psychological well-being are studied as a part of scientific psychology and have practical significance.Purpose and tasks. The purpose of the study is to identify and describe the personal factors of the psychological well-being of Ukrainian female forced migrants.M e t h o d s . Applied methods of theoretical analysis, synthesis, and generalization, as well as several empirical test methods.R e s u l t s . It was determined that migration is a multi-stage process unfolding over time, containing many psychological aspects, and accompanied by the transformation of the entire system of social-psychological relations, which leads to a significant strain on psychological mechanisms. It affects the general level of psychological well-being of migrants, which we see as a resource and a result of migrants' coping strategy to soothe the stress and adapt to the migration state.It has been empirically proven that psychological well-being has a connection with psychological resourcefulness and coping strategies: aimed at solving the problem, expressing emotions, avoidance, and intolerance of uncertainty.C o n c l u s i o n s . The level and factors of psychological well-being of Ukrainian female forced migrants were studied. Data analysis shows that most Ukrainian females in forced migration show an average level of psychological well-being. Among its factors are internal personal factors, in particular, psychological resourcefulness, strategies for overcoming stressful and difficult situations aimed at solving problems and responding to emotions, as well as tolerance of uncertainty.It is necessary to develop and promote a corrective, supportive, and preventive program (for the secondary prevention of stressful conditions).The aim is to develop and support the psychological well-being of Ukrainian females in forced migration.
Keywords: migration; coping with stress; psychological well-being; tolerance of uncertainty; psychological resourcefulness; coping strategies; prevention of stressful conditions